2021
DOI: 10.17341/gazimmfd.784968
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dispute factors and effects on construction projects arising from Covid-19 pandemic as a force majeure event

Abstract: Investigation of the dispute factors and their effects on construction projects that are arising from Covid-19  Determination of the relations between the dispute factors and their effects using Structural Equation Modeling (SEM) method  Identification of approaches that should be applied to reduce the effects of the disputes arising from Covid-19 in construction projectsFigure A. Results of Structural Equation Modeling AnalysisPurpose: The purpose of this study is to investigate the effects of Covid-19 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…It has also created various uncertainties in the management of contracts for construction projects (Kabiru and Yahaya, 2020;Rospigliosi et al, 2020;Sierra, 2021). Aladag et al (2021) stated that COVID-19 would cause the project cost to explode and made it impossible to perform the tasks stipulated in the previous contract. Hansen (2020) attempted to explore the possibility of COVID-19 as a force majeure event for construction contracts.…”
Section: Ecam 308mentioning
confidence: 99%
See 2 more Smart Citations
“…It has also created various uncertainties in the management of contracts for construction projects (Kabiru and Yahaya, 2020;Rospigliosi et al, 2020;Sierra, 2021). Aladag et al (2021) stated that COVID-19 would cause the project cost to explode and made it impossible to perform the tasks stipulated in the previous contract. Hansen (2020) attempted to explore the possibility of COVID-19 as a force majeure event for construction contracts.…”
Section: Ecam 308mentioning
confidence: 99%
“…After all, the boundary between force majeure, impossible, difficult and impractical contracts were still very delicate at present. Aladag et al (2021) suggested that both contractors and owners should carefully review their contracts to avoid disputes related to COVID-19, especially the provisions on force majeure. Construction companies should not only focus on short-term impacts but also take long-term considerations to reduce possible disputes related to COVID-19.…”
Section: Impacts Of Covid-19 On Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spending less time on-site can lead employees to feel that their role is marginalized within the company (Pearson, 2021). Therefore, project efficiency can decline due to changes in working hours and quarantine measures (Aladağ et al. , 2021).…”
Section: Research Backgroundmentioning
confidence: 99%
“…(2021), 44.8% of respondents in West Sumatra Province, Indonesia noted that the labor distribution was worse during the pandemic period compared to normal conditions. Employers have also encountered difficulties in getting their monthly payments (Aladağ et al. , 2021), as most of the projects have slowed down or ceased.…”
Section: Research Backgroundmentioning
confidence: 99%